Implications Of Political Uncertainty Periods on Stock Returns in the Property and Real Estate Sector - Ikhsan Bagaskoro; Suhita Whini Setyahuni; Maria Safitri; Pradana Jati Kusuma (International Journal of Economics, Management and Accounting, 2025)
This study aims to assess how financial performance influences stock returns amid political uncertainty, specifically during the 2024 general election in Indonesia. The focus is on understanding the impact of various financial performance indicators on the stock returns of property and real estate firms listed on the Indonesia Stock Exchange. A sample of 64 companies was observed during two critical periods: the pre-election period in the fourth quarter of 2023 and the post-election period in the second quarter of 2024. To analyze the data, the study employed an event study approach, utilizing multiple regression analysis to identify the relationship between financial performance and stock returns, and paired sample t-tests to compare pre- and post-election performance. The findings revealed that prior to the election, the variables Return on Assets (ROA), Debt to Equity Ratio (DER), and Revenue Growth did not significantly affect the stock returns of property and real estate companies. However, after the election, only ROA was found to have a significant impact on stock returns, while DER and Revenue Growth continued to show no effect. A comparative analysis of the two periods indicated no significant differences in the financial performance variables (ROA, DER, and Revenue Growth) between the pre- and post-election periods, yet a clear shift in stock returns was observed. This study contributes to the literature by offering a fresh perspective on how political uncertainty affects stock returns, using the framework of signaling theory, trade-off theory, and market efficiency theory to interpret the results.